HPLCTOXICOLOGICAL SCREENING METHOD BY HPLC TOXICOLOGICAL SCREENING METHOD BY HPLC TOXICOLOGICAL SCREENING METHOD BY HPLC TOXICOLOGICAL SCREENING METHOD BY HPLCTOXICOLOGICAL SCREENING METHOD BY HPLC TOXICOLOGICAL SCREENING METHOD BY HPLC TOXICOLOGICAL SCREENING METHOD BY HPLCTOXICOLOGICAL SCREENING METHOD BY HPLCTOXICOLOGICAL SCREENING METHOD BY HPLC TOXICOLOGICAL - Khaled, Sobhi*; Souhila r, Mélaïne; Mohamed, Mammar (university of eloued جامعة الوادي, 2022)
A liquid-liquid extraction technique and HPLC-DAD method using a C18 column, 5μm (150x4.6mm i.d.) were developed for a toxicological drug screening. A home-made “N-acetylparoxetine” is used as internal standard. A local UV spectra library of over 130 drugs and some of their metabolites was created. This library covers the main therapeutic classes involved in intoxication cases. The developed procedure is successfully applied to different biological samples (serum, urine, gastric fluid and post mortem whole blood) and allows rapid and simultaneous detection and identification of a large number of substances and their semi-quantification in serum.
artical
Keywords: HPLC-DAD, LLE, drug poisoning, systematic toxicological analysis.